TINGKAT RUJUKAN EMISI HUTAN MANGROVE DELTA MAHAKAM - Frida Sidik; Bambang Supriyanto; Mega Lugina (Jurnal Analisis Kebijakan Kehutanan, 2017)
Forest Reference Emission Level (FREL) is one of four required elements for developing countries in  implementing REDD+ activities, and serves  as a benchmark in assessing  REDD+ performance. This study assessed the emission level from mangrove deforestation in Mahakam Delta - East Kalimantan, aiming to enhance the baseline for subnational FREL document. Over the observation period of 1980-2001, conversion of mangrove forest into aquaculture ponds has resulted in a massive mangrove loss, with an estimation of  3,183 hectare/year, or equivalent to the release of 0.46 Tg CO2e/year. If soil pool was also  included in the calculation, mangrove deforestation in Mahakam Delta between 1980 and 2001 emitted 2.9 TgCO2e/year. The CO2 emission from aquaculture ponds may couple with mangrove deforestation, which released 52 Gg CO2 /year from the pond floor. After 2001, the rate of mangrove deforestation decreased, allowing mangrove forests to recover with the expansion rate of 1,546 hectare/ year during 2001-2011 or equivalent to the carbon sequestration or removal of 0.67-4.7 TgCO2e/year. The results of the study suggest the way to improve the existing FREL by raising the importance of mangrove as “blue” carbon, with reference of the 2013 IPCC Guideline: Wetland Supplement.